Talking about work during a manicure appointment – a study at the intersection of conversation analysis and cognitive linguistics - Rancew-Sikora, Dorota; Steciąg, Magdalena (Papers in Linguistics, 2025)
The article juxtaposes parallel analyses of one research material from two different perspectives – conversation analysis, rooted in social sciences, and cognitive linguistics, one of the branches of linguistics. The material is a spontaneous conversation conducted during a manicure appointment. Since the main topic of the conversation is work, the attention is focused, firstly, on its role in the dynamics of the interaction and relationship between the participants, and secondly, on the reconstruction of the metaphorical image of work that emerges from the conversation. The aim of the article is not only to analyse the structure of the conversation and its meaning due to the specific institutional context, but also to look back at analytical tools and research methods. Both presented approaches see human experiences as grounded in material space and tangible nature, which are a source of both cognitive metaphors and basic interactional competencies. An analysis at the “intersection” of the disciplines shows the value of interdisciplinary systems in research projects aimed at searching for new paths within existing approaches.